Arctic Tundra Caribou and Climatic Change: Questions of Temporal and Spatial Scales - Ferguson, Michael (Geoscience Canada, 1996)
Summary Climatic changes have affected populations of caribou and reindeer {Rangifer tarandus) at scales ranging from a single winter to tens of thousands of years, and from micro-habitats to entire continents. Individuals, populations and the species have adapted to these climatic changes, however, producing complex evolutionary and ecological issues requiring multi-scale, interdisciplinary research. Caribou populations wintering on arctic tundra may be most susceptible to the impacts of anthropogenic climatic change, given the low productivity of their for age, the severity and duration of the winters, and the physical barriers that limit dispersal. Subspeciation of Rangifer tarandus hypothetical^ occurred during the Wisconsin glaciation. Recent genetic analyses support the current classification of subspecies, except that Baffin Island caribou may be distinct from barren-ground caribou, R. t. groenlandicus, on mainland Northwest Territories. Baffin caribou may have originated from a small ancestral population in a refugium on Baffin Island during the Wisconsin glaciation; or, they may have originated from immigrants after the Wisconsin glaciation, later experiencing a severe population bottleneck. On a shorter time scale, recent research has suggested that density-independent climatic events occurring over a single winter have caused at least one major population decline among Peary caribou on the Queen Elizabeth Islands. Dramatic fluctuations of Greenland populations over the past 200 years have been attributed to climatic changes. However, the onset of some population changes on western Greenland have been inconsistent with the timing of climatic changes. Inuit knowledge of Baffin caribou and studies of tundra caribouon Svalbard, Coats and Southampton islands, South Georgia, and Norway suggest that caribou populations are affected primarily by density-dependent grazing impacts on forage that can lastseveral decades. The discrepancy between these views may be caused by differences in the temporal and spatial scales over which scientific investigations have been conducted, and the measurement of only some ecological factors.Arctic ecological studies require extensive spatial and temporal data before impacts of anthropogenic climate change can be assessed.This will require a long-term interdisciplinary study integrating scientific data from several disciplines, as well as Inuit knowledge.